(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article discusses the possibility of using the method of art anthropology in the literary works of N.V. Gogol; artistic concepts are presented from the perspective of anthropology as a research direction and method of scientific investigation as a synthesis of the author`s concept of human rights and a special type of artistry. Viewed from this perspective, art anthropology of Gogol revealed, on the one hand, the influence of Christianity, on the other hand, as a consequence of this effect, the two dominant trends - antinomy.